Peran Guru dalam Menangani AUD yang Mengalami Gangguan Keterlambatan Berbicara (Speech Delay) di PAUDQU Al Falah - Siti Adawiah; Komariah Komariah; Wini Yuliantika (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2024)
This research aims to find out the role of teachers in dealing with young children who experience speech delay at PAUDQU Al-Falah. The research method used is descriptive qualitative, namely by describing what researchers do during observations, interviews and observations. The data collection techniques used were observation and interviews by asking questions that had been prepared. After the data was obtained from observations and interviews, descriptions and analyzes were carried out regarding what was obtained. The results of the research show that the teacher's role in overcoming speech barriers includes: speaking clearly by showing correct hand movements and articulation, repeating simple words and paying attention to the grammar of what is spoken, training children to speak correctly repeatedly and slowly when speaking. always pay attention to the language vocabulary used by the child or spoken by the child, children speak every time in any situation by controlling, correcting what the child says when the child makes a mistake in pronouncing the vocabulary accompanied by their parents or someone close to them.